The development of the Dutch version of the Fremantle Back Awareness Questionnaire. (December 2017) - Janssens, Lotte; Goossens, Nina; Wand, Benedict M.; Pijnenburg, Madelon; Thys, Tinne; Brumagne, Simon
Abstract: Background: Disturbed body perception may play a role in the aetiology of chronic low back pain (LBP). The Fremantle Back Awareness Questionnaire (FreBAQ) is currently the only self-report questionnaire to assess back-specific body perception in individuals with LBP. Objectives: To perform a cross-cultural adaptation of the FreBAQ into Dutch. Design: Psychometric study. Methods: A Dutch version of the FreBAQ was generated through forward-backward translation, and was completed by 73 patients with LBP and 73 controls to assess discriminant validity. Structural validity was assessed by principal component analysis. Internal consistency was assessed by the Cronbach's alpha coefficient. Construct validity was assessed by examining the relationship with clinical measures (Numerical Rating Scale pain, Oswestry Disability Index (ODI), Tampa Scale for Kinesiophobia). Test-retest reliability was assessed in a subgroup (n = 48 with LBP and 48 controls) using intraclass correlation coefficients (ICC), standard error of measurement (SEM) and minimal detectable change (MDC 95%) Results: The Dutch FreBAQ showed one component with eigenvalue >2. Cronbach's alpha values were respectively 0.82 and 0.73 for the LBP and control group. ICC values were respectively 0.69 and 0.70 for the LBP and control group. In the LBP group, the SEM was 3.9 and the MDC (95%) was 10.8. The LBP group (ODI 22 ± 21%) scored significantly higher on the Dutch FreBAQ than the control group (ODI 0%) (11 ± 7 vs. 3 ± 9, p < 0.001). Within the LBP group, higher Dutch FreBAQ scores correlated significantly with higher ODI scores (rho = 0.30, p = 0.010), although not with pain (rho = 0.10, p = 0.419) or kinesiophobia (r = 0.14, p = 0.226). Conclusions: The Dutch version of the FreBAQ can be considered as unidimensional and showed adequate internal consistency, sufficient test-retest reliability and adequate discriminant and construct validity in individuals with and without LBP. It can improve our understanding on back-specific perception in the Dutch-speaking population with LBP. Highlights: A Dutch version of the Fremantle Back Awareness Questionnaire (FreBAQ) was developed. The Dutch FreBAQ shows sufficient test-retest reliability. The Dutch FreBAQ discriminates between individuals with and without low back pain. It improves our understanding on back-specific perception in low back pain.